Motivation in sport and exercise: a comparison between the BRSQ and BREQ - Rodrigues, F (2021)
This study aimed to test whether the Behavioral Regulation in Sport Questionnaire and the Behavioral Regulation in Exercise Questionnaire can measure the same constructs in an equivalent manner. Advanced statistical procedures were used to examine if these scales could be interchangeably applied to the sport and the exercise context. In total, 2256 indi- viduals (athletes = 1099; exercisers = 1157) completed translated and validated question- naires measuring all types of motivation based on Self-Determination Theory. Several measurement models were tested, such as confirmatory factor models, exploratory struc- tural equation models, and bifactor specifications. The exploratory structural equation modelling approach provided the best fit to the data in both groups. Multigroup analysis was performed within samples and between athletes and exercisers. Measurement model invariance was confirmed between samples from the same context; however, it did not achieve equivalence between scales. We hope this examination of context invariance analy- sis using specific validated scales can further help advance conceptual understanding of the measurement in sport and exercise.